Forest recovery pathways after fire, drought, and windstorms in southeastern Amazonia - Leandro Maracahipes; Paulo M. Brando; Divino V. Silvério; Leonardo Maracahipes-Santos; Antônio C. Silveiro; Larissa Verona; Marcia N. Macedo; Susan Trumbore; Eddie Lenza; Bela Starinchak; Nathalia Potter; David Herrera-Ramírez; et al. (Proceedings of the National Academy of Sciences, 2026)
The future of tropical forests depends on their ability to resist and recover from multiple disturbances. Here, we evaluated how edge effects, experimental fires, extreme droughts, and blowdowns reshaped forest structure, composition, and functional traits over two decades in the Amazon–Cerrado transition. Initially, forests resisted low-intensity fires, but subsequent high-intensity fires during severe droughts sharply increased susceptibility to further disturbances. Along forest edges bordering agriculture, these compound disturbances drove losses of tree species richness, declines in Amazonian forest-specialist species, and shifts toward generalists with broad distributions, indicating increased compositional homogenization (i.e., reduced taxonomic diversity and dominance of generalist species). Once fires ceased, recovery trajectories diverged: Interior forests rapidly regained woody species richness and composition, whereas edge forests recovered more slowly. During postfire recovery, embolism-resistant species (lower P50 values) became more common, yet communities exhibited lower hydraulic safety margins (increased vulnerability to drought). At the same time, generalist species remained abundant, forest-specialist declined, and only a single woody species typical of savanna was established. Although grasses initially colonized fire-altered edges—especially light-demanding exotic Andropogon gayanus —they declined once fires stopped, leaving only small patches of shade-tolerant C3 species. Consequently, we find little evidence that fire-degraded forests transition toward persistent savanna, although recurrent fires or future climatic changes could drive long-lasting degradation or human-derived savannas. Together, these results show that even highly degraded, grass-invaded forests can recover in the absence of new disturbances, but the communities that reassemble remain vulnerable to renewed fire, drought, or windthrow.